Dosimetric characteristics of fabricated ge-doped silica optical fibres for small field radiation dosimetry in radiotherapy - Lam, Siok Ee (2019)
Advances in radiation treatments have resulted in the increased use of small treatment fields with millimeter scale and high dose in treating small tumours. The determination of absorbed dose may not be as accurate as previously achieved for the standard radiotherapy applications using broad treatment fields due to the presence of charged particle disequilibrium, occlusion of the primary radiation source and volume averaging effect of dosimeter. This study is pertaining to the potential of the locally fabricated 6 mol% Germanium-doped (Ge-doped) silica fibres to be utilised in the small-field dosimetry. Three fibre types, cylindrical fibres (CF) (483 µm) and flat fibres (FF) (273 x 67 µm2 ) fabricated from the 6 mol% Gedoped preform and commercial Ge-doped 50 µm-core fibres (COMM), were used. The time-temperature profiles (TTP) for the fibre readouts and the effect of TTP on the kinetic parameters of the glow curves as well as the dosimetric characteristics of fabricated Ge-doped silica fibres were investigated prior to the output factors study of a dedicated linear accelerator. A constant TTP (preheat 80 °C and heating rate 30 °Cs-1 ) was employed in all fibre readouts due to the centrally distributed glow curves enabling complete capture of the thermoluminescent (TL) glow curve, the stability of this situation across three fibre types and the near proportionality of peak integral and peak temperature of the deconvoluted glow peaks. Two Perspex phantoms were custom-made for the studies of angular dependency and output factors of the fibres. The FF offer superior performance compared to that of the CF in terms of dose repeatability (2% to 6%), angular independence (± 3%) and dose-rate independence. For doses up to 80 Gy delivered using 6 MV photon beams, the FF exhibit a highly linear dose response (R2  99%). While both CF and FF were pulled from the same preform, the CF have been found to contain greater Ge concentration (2.58 ± 0.18 wt%) as compared to that of the FF (1.45 ± 0.15 wt%) due to the difference in Energy Dispersive X-ray Spectroscopy line scanned on these two different shaped fibres. The dose sensitivity of FF with the least dose variability in 3 x 3 cm2 and 10 x 10 cm2 fields is adequate for the current intended use in high-dose advanced radiotherapy. The notable signal fading of the fabricated fibres (25% for FF; 34% for CF) over the period of 31 days post-irradiation with a dose of 5 Gy would need to be carefully accounted for in small-field application. The Independent T-Test shows there to be no significant difference between the normalised TL responses measured for each fibre type (p values 0.05) in 3 x 3 cm2 and 10 x 10 cm2 fields. The output factors measured using FF (0.69 to 0.99) in the circular fields (6 to 15 mm) are much higher than those of CF, radiochromic EBT3 and ionization chamber CC01, with the exception of 4 mm field where output of FF is comparable to that of EBT3 (output of EBT3 is 1.15x the output of FF). This study provides a promising support for the viability of fabricated fibres, particularly FF as an optical-fibre based dosimeter for use in small-field dosimetry.